Acaulospora paulinae, a new record of arbuscular mycorrhizal fungal species from Telangana state, India - Prasad, K. Hari; Hindumathi, A.; Bhadraiah, B. (International Journal of Scientific Research in Biological Sciences, 2019)
Acaulospora paulinae was isolated from the rhizosphere soils of Setaria italica (Poaceae), Emilia sonchifolia and Vernonia cinerea (Asteraceae) from Nagarkurnool and Wanaparthy Districts, Telangana, India. The spores are globose to subglobose, 60-95µm in diameter. Sometimes ovoid 60-70 X 80-95 µm. Hyaline to sub hyaline or pale yellow. The spore wall composed of three layers. The surface of the middle layer is ornamented with evenly distributed pits 2.0-2.5 X 3.0-3.5 µm. A. paulinae spores were found in sandy loam soils with decreasing spore numbers. A. paulinae is a characteristic member of the arbuscular mycorrhizal fungal communities in soils with pH 5.3-8.5 in sandy loam soils of Nagarkurnool and Wanaparthy Districts, Telangana, India